Rhesus Cytomegalovirus-Specific CD8+ Cytotoxic T Lymphocytes Do Not Become Functionally Exhausted in Chronic SIVmac239 Infection - Rosen, Brandon C.; Pedreño-Lopez, Nuria; Ricciardi, Michael J.; Reed, Jason S.; Sacha, Jonah B.; Rakasz, Eva G.; Watkins, David I. (Frontiers in Immunology, 2020)
CD8+ cytotoxic T lymphocytes (CTLs) exert potent antiviral activity after HIV/SIV infection. However, efforts to harness the antiviral efficacy of CTLs for HIV/SIV prophylaxis and therapy have been severely hindered by two major problems: viral escape and exhaustion. By contrast, CTLs directed against human cytomegalovirus (HCMV), a ubiquitous chronic herpesvirus, seldom select for escape mutations and remain functional and refractory to exhaustion during chronic HCMV and HIV infection. Recently, attempts have been made to retarget HCMV-specific CTLs for cancer immunotherapy. We speculate that such a strategy may also be beneficial in the context of HIV/SIV infection, facilitating CTL-mediated control of HIV/SIV replication. As a preliminary assessment of the validity of this approach, we investigated the phenotypes and functionality of rhesus CMV (RhCMV)-specific CTLs in SIVmac239-infected Indian rhesus macaques (RMs), a crucial HIV animal model system. We recently identified two immunodominant, Mamu-A*02-restricted CTL epitopes derived from RhCMV proteins and sought to evaluate the phenotypic and functional characteristics of these CTL populations in chronic SIVmac239 infection. We analyzed and directly compared RhCMV- and SIVmac239-specific CTLs during SIVmac239 infection in a cohort of Mamu-A*01+ and Mamu-A*02+ RMs. CTL populations specific for at least one of the RhCMV-derived CTL epitopes were detected in ten of eleven Mamu-A*02+ animals tested, and both populations were detected in five of these animals. Neither RhCMV-specific CTL population exhibited significant changes in frequency, memory phenotype, granzyme B expression, exhaustion marker (PD-1 and CTLA-4) expression, or polyfunctionality between pre- and chronic SIVmac239 infection timepoints. In chronic SIVmac239 infection, RhCMV-specific CTLs exhibited higher levels of granzyme B expression and polyfunctionality, and lower levels of exhaustion marker expression, than SIVmac239-specific CTLs. Additionally, compared to SIVmac239-specific CTLs, greater proportions of RhCMV-specific CTLs were of the terminally-differentiated effector memory phenotype (CD28– CCR7–) during chronic SIVmac239 infection. These results suggest that, in contrast to SIVmac239-specific CTLs, RhCMV-specific CTLs maintain their phenotypes and cytolytic effector functions during chronic SIVmac239 infection, and that retargeting RhCMV-specific CTLs might be a promising SIV immunotherapeutic strategy.